Artificial Intelligence and Cognitive Science 30th Irish Conference, AICS 2022, Munster, Ireland, December 8-9, 2022, Revised Selected Papers - Longo, Luca; O'Reilly, Ruairi (Communications in Computer and Information Science,, 2023)
This open access book constitutes selected papers presented during the 30th Irish Conference on Artificial Intelligence and Cognitive Science, held in Munster, Ireland, in December 2022. The 41 presented papers were thoroughly reviewed and selected from the 102 submissions. They are organized in topical sections on machine learning, deep learning and applications; responsible and trustworthy artificial intelligence; natural language processing and recommender systems; knowledge representation, reasoning, optimisation and intelligent applications.